The Milk Deity IAt ('I3At) in Ancient Egyptian Religion - Ahmed, Ayman Mohamed.
This paper addresses the question of the deity (I3t/I3ty) in ancient Egyptian religion. To date, there has not been a comprehensive study of this deity. The author attempts to provide answers for questions concerning how the name was written, differentiating the male and female forms of the deity, outlining the deity’s character, describing his/her physical appearance and attributes, and his/her link to divine birth and milk production. Several issues related to this deity, such as its dual nature, remain uncertain. For example, although textual resources indicate a female form of the deity, no female form is actually shown. This study, based on linguistic, theological, and archeological sources, presents more documentation of this little-known deity in hope that it will serve as the basis for further research.doi: http://dx.doi.org/10.5913/jarce.56.2020.a001